Russian revolutionary posters from civil war to socialist realism, from Bolshevism to the end of Stalin - King, David 1943-2016 (Tate Publ., 2012)
This book tells the story of the development of the Soviet poster, from the revolutionary period through to the death of Stalin, revealing the way in which tumultuous events within the Soviet Union were matched by equally dramatic shifts in graphic art and design. Written and designed by David King, one of the world's foremost experts on Soviet art and himself an internationally acclaimed graphic designer, the publication features posters drawn from his unparalleled collection, well known to visitors to Tate Modern in London. The book is arranged chronologically. Captions accompany each poster, explaining the historical and artistic context in which it was produced. Constructivist posters, socialist advertising, film posters of the 1920s, classic photo-montage, the heroic posters of the Great Patriotic War, biting political satire and the cult of personality of the Stalin years are all here
Keywords: Geschichte 1917-1953; Plakat; Revolution -- Motiv; Sowjetunion; Bildband